O DISCURSO ORGANIZACIONAL E OS DEFICIENTES NAS MÍDIAS DIGITAIS: A CONSTRUÇÃO DE REPRESENTAÇÕES - OLIVEIRA, MONIQUE ARAUJO DE (2018)
The dialog between the brands and disabled consumers is challenging, since it is not enough to seek attractions, companies should also take into consideration customers' physical and intellectual limitations. Even more considering the whole history of this relationship, which exposes exclusion, a silenced dialogue and without representativeness. The study has the objective of confronting the organizational communication aimed at the disabled public with the evaluation that this group makes of this discourse, that is, whether or not it is represented there. This is a qualitative research, subsidized by Discourse Analysis of the french line, with emphasis on concepts such as ethos, páthos and scenes of enunciation. Initially, a monitoring of the social media and news and official sites of five selected companies, according to criteria based on the evaluation of Você S/A Magazine, with the 150 Best Companies to Work for 2015, allows to investigate how such organizations promote, in addition to punctuating the image they make of disabled clients through the analysis of sustainability reports and publications on activities aimed at this public. In a second moment, the application of focus groups and individual interviews in entities that work with people with disabilities mentions the picture of how they are represented, highlighting the collision of distorted images, with a discourse that distances itself from the practice, and which does not dialogue because of the lack of attention to their demands and needs. The counterpoint among the stages reinforces the lack of interest of the majority of companies in providing a more inclusive communication and a customized customer service, mainly represents the lack of visibility and devaluation of the potential of these consumers in the market, which also reflects in society